Development of QPEC (Questionnaires Package for Engineering Curriculum) and SAS (Statistical Analysis System) to analyse the survey [case study: Market survey for curriculum development of Bachelor Engineering (hons) in Mechanical (Manufacturing)] / Dr Zahurin Halim, Nor Hayati Saad and Suhaimie Sapari. - Halim, Zahurin (Dr.); Saad, Nor Hayati; Sapari, Suhaimie (2006)
The nation is progressing towards the Vision 2020 to become a developed nation. One of the very important aspects to progress towards this vision is the development of the technology and manpower to support the country progression. It is found that the manufacturing sector becomes one of the main contributors for the Malaysian industry. After Malaysia gained independence in 1957, the development of the manufacturing sector took priority. From the mid-1970s to mid-1990s Malaysia had one of the world's fastest-growing economies, mainly due to rapid industrialization. Therefore, to continuously support the sector, it is necessary to upgrade the technological skills of the nation through its manpower. The government needs to formulate, implement and support an aggressive education policy targeted to higher level of the manufacturing program to educate managerial and technical experts that are dedicated to work in the industry. This research attempts to discuss the potential of the manufacturing sectors and the needs of the country to invest in higher level of manufacturing program toward the country's goal. The result of the market survey that had been done to 30 companies in Malaysia, and to 238 students are analyzed to determine the demands on the program. From the analysis of the survey, it was found that it is very crucial for the higher learning institution to expedite the program development related to manufacturing area due to the needs of the nation, country, as well as the manufacturing sector to compete in the global world market.